Prospect of Ubiquitous Power Internet of Things in Electricity Market - Chaopeng XIA (发电技术, 2020)
With the deepening of power system reform, power customers have acquired the ability to participate in power trading with emerging technologies such as distributed generation, energy storage systems and electric vehicles. However, the operation and control methods of traditional power systems are difficult to adapt to the demand of open electricity market in the new era. The strategy of ubiquitous power internet of things (UPIoT) proposed by State Grid Co., Ltd. can realize the interconnection of all aspects in power system, overall state perception and optimal control, which is an effective technical support for building an open electricity market. The challenges faced by the development of power systems in the new era and the necessity of constructing UPIoT were analyzed. The typical application of UPIoT in the open electricity market was researched. Finally, the key technologies of UPIoT for the electricity market were discussed, which provide reference for constructing modern open electricity market.